Impact on dosimetry of occupationally exposed individuals on the patient management for PET/MRI studies: a comparison study with dosimetry on PET/CT (Brazilian Journal of Radiation Sciences (BJRS), 2023)
PET/MRI technology has expanded the boundaries of investigation in nuclear medicine, supported by the high sensitivity of solid-state PET detectors. Nonetheless, the coil positioning might lead to an increased exposure period of the worker to the injected patient. This procedure does not occur on PET/CT and, therefore, exposure period is reduced on such scanner. The aim of our study was to evaluate the dosimetry of two occupationally exposed individuals (OEI) working at the Center of Nuclear Medicine of Hospital das Clínicas of the University of Sao Paulo. We used thermoluminescent (TLD) dosimeters in pulse, whole-body and crystalline for PET/MRI and PET/CT procedures during five months of clinical and research routine. We also monitored the time for positioning/removing the patient on both scanners. For this study, OEI1 performed 76 PET/MRI studies and 102 PET/CT studies while OEI2 performed 26 and 56 PET/MRI and PET/CT studies, respectively. We found no evidence of differences for the whole-body dose values between both scanners (p = 0.22). The average time of patient management (positioning/removing the patient) was 14.38, and 3.81 minutes for PET/MRI and PET/CT, respectively. When the normalization by the number of PET/CT studies was applied, we found no statistical difference for effective and equivalent dose values. Our study encourages future investigations on nursing staff, which is a critical population that is exposed to ionizing radiation, mainly on dynamic studies, due to the synchronized injection with the protocol starting.